ASSESSMENT OF COMPOST AS NUTRIENT SUPPLEMENT FOR SPRING PLANTED SUGARCANE (SACCHARUM OFFICINARUM L.) - M. Nawaz; M. U. Chattha; M. B. Chattha2; R. Ahmad; H. Munir; M. Usman; M.U. Hassan; S. Khan; M. Kharal (Journal of Animal and Plant Sciences, 2017)
The sustainable agriculture production is only possible through good soil health attainted through balanced use of organic and inorganic fertilizers. The imbalanced fertilizer application is a major cause of low sugarcane yield and deterioration of soil. A field experiment was conducted to evaluate the effect of combined application of compost and inorganic fertilizers on spring planted sugarcane for two consecutive years (2013-14 and 2014-15) at the Research Farm, Shakarganj Sugar Research Institute (SSRI) Jhang, Pakistan. Experiment was comprised of different compost and fertilizer combinations viz. compost (1124 kg ha-1) alone, fertilizer (168:112:112 kg NPK ha-1) alone, compost (843 kg ha-1) + fertilizer (42:28:28 kg NPK ha-1), compost (562 kg ha-1) + fertilizer (84:56:56 kg NPK ha-1), compost (281 kg ha-1) + fertilizer (126:84:84 kg NPK ha-1) and compost (1124 kg ha-1) + fertilizer (42:28:28 kg NPK ha-1). The study was managed under randomized complete block design with three replications. Sugarcane variety S2003-US-114 (CPF-248) was used as medium for the trial. Results revealed the average maximum leaf area index (7.73), crop growth rate (11.19) and net assimilation rate (2.47) recorded from combined application of compost (1124 kg ha-1) with fertilizer (42:28:28 kg NPK ha-1). Highest average number of millable canes (14), cane length (260 cm), weight per stripped cane (0.86 kg), un-stripped cane yield (138.42 t ha-1), stripped cane yield (116.27 t ha-1) and sugar recovery (13.49%) were recorded in compost (1124 kg ha-1) + fertilizer (42:28:28 kg NPK ha-1) followed by compost (562 kg ha-1) + fertilizer (84:56:56 kg NPK ha-1) and fertilizer alone at (168:112:112 kg NPK ha-1) during both the years. There was minute difference in yield among the years due to change in environmental conditions during both crop growing season. The average maximum benefit cost ratio 1.78 was also gained from compost (1124 kg ha-1) + fertilizer (42:28:28 kg NPK ha-1) application.
Keywords: Sugarcane; Compost; NPK; Cane yield; Sugar recovery; Economic analysis